Evaluation of Online Learning During COVID-19 - Dwi Atmanti, Hastarini; ., Caroline; Kadang, Juliana (KnE Social Sciences, 2022)
This study aims to evaluate the effects of online learning during the pandemic on economics students at two different institutions, Diponegoro University and Tadulako University. Diponegoro University (UNDIP) represents universities in the West region, and Tadulako University (UNTAD) represents universities in the Eastern region of Indonesia. This study used descriptive qualitative analysis to describe the implementation of online learning during the COVID-19 pandemic at the two different institutions. Based on the results of the analysis, students on both campuses use learning applications to carry out distance lectures. The obstacle that is often faced by students is that it is difficult to signal to be able to attend online lectures. Students also remain active in class, even though the learning is online. Keywords: Online learning; covid pandemic 19; UNDIP; UNTAD